Mechanisms of chronic rejection in cardiothoracic transplantation - Weiss, Matthew J. (2008)
Despite significant improvements in early post-transplantation survival rates, long-term patient and graft survival have remained poor, due in large part to the vexing problem of chronic allograft rejection. Attempts to combat this problem with intensification of immunosuppression have led to concomitant increases in the rates of fatal malignancies and infections. In cardiac transplantation, chronic rejection is manifested primarily by a disease entity known as cardiac allograft vasculopathy, an occlusive narrowing of the coronary vessels. In lung transplantation, chronic rejection is typified by obliterative bronchiolitis, an airflow limiting narrowing of the bronchioles. From an immunologic standpoint, chronic rejection is believed to be the end result of repeated immune and non-immune insults to the graft. This review examines the pathophysiology of heart and lung chronic, with emphasis on both immune and non-immune causes.